2005
DOI: 10.1128/aem.71.11.7551-7555.2005
|View full text |Cite
|
Sign up to set email alerts
|

Strain- and Genotype-Specific Differences in Virulence of Paenibacillus larvae subsp. larvae , a Bacterial Pathogen Causing American Foulbrood Disease in Honeybees

Abstract: Virulence variations of Paenibacillus larvae subsp. larvae, the causative agent of American foulbrood disease of honeybees, were investigated by analysis of 16 field isolates of this pathogen, belonging to three previously characterized genotypes, as well as the type strain (ATCC 9545) of P. larvae subsp. larvae, with exposure bioassays. We demonstrated that the strain-specific 50% lethal concentrations varied within an order of magnitude and that differences in amount of time for the pathogen to kill 100% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
252
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(267 citation statements)
references
References 18 publications
6
252
1
3
Order By: Relevance
“…Nevertheless, the influence of bee subspecies on their susceptibility could be the subject of further investigation. Finally, there may be distinctions in the virulence of the haplotypes of N. ceranae (Williams et al, 2008a, b) similarly to the genotype-specific ones of Paenibacillus larvae (Genersch et al, 2005Ashiralieva and Genersch, 2006 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the influence of bee subspecies on their susceptibility could be the subject of further investigation. Finally, there may be distinctions in the virulence of the haplotypes of N. ceranae (Williams et al, 2008a, b) similarly to the genotype-specific ones of Paenibacillus larvae (Genersch et al, 2005Ashiralieva and Genersch, 2006 …”
Section: Discussionmentioning
confidence: 99%
“…Since then a wide range of strains of P. larvae that all cause the typical AFB symptoms have been described. Recently Genersch et al (2006) identified four genotypes (ERIC I to ERIC IV) of these bacteria with different levels of virulence (Genersch et al 2005(Genersch et al , 2006.…”
Section: History Of the Identification Of Afb As A Honeybee Diseasementioning
confidence: 99%
“…This disease causes the decline of the population. American foulbrood can also lead to the death of the colony (Genersch et al, 2005;Santos et al, 2012). The causative agent is Paenibacillus larvae (White), a gram positive and sporeforming bacterium that is distributed worldwide (Spivak and Reuter, 2001;Genersch et al, 2006).…”
mentioning
confidence: 99%